2009
DOI: 10.4161/cc.8.1.7527
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of p27Kip1gene transcription by mitogens

Abstract: How mitogens reduce the abundance of the cell cycle inhibitor p27 Kip1 is an important question, and regulation of p27 Kip1 translation and turnover has been described. Here we show that platelet-derived growth factor (PDGF) reduces the activity of the p27 Kip1 promoter and the abundance of the p27 Kip1 transcript in density-arrested mouse fibroblasts. Inhibition of p27 Kip1 gene expression by PDGF required protein synthesis and histone deacetylase activity but not Akt or ERK activity. PDGF increased the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 70 publications
0
21
0
5
Order By: Relevance
“…It has been reported that concanavalin A and IL-2 stimulation transcriptionally decrease the abundance of CDKN1B. 40 However, there was no difference in the expression of Cdkn1b at the mRNA level between floxed control and autophagy-deficient T cells (data not shown). IL-7 promotes T cell proliferation through the regulation of stability of CDKN1B at the protein level, which is dependent on PRKCQ/ PKC-u (protein kinase C, theta).…”
Section: Autophagy-deficient T Cells Fail To Enter Into S Phase Aftermentioning
confidence: 76%
“…It has been reported that concanavalin A and IL-2 stimulation transcriptionally decrease the abundance of CDKN1B. 40 However, there was no difference in the expression of Cdkn1b at the mRNA level between floxed control and autophagy-deficient T cells (data not shown). IL-7 promotes T cell proliferation through the regulation of stability of CDKN1B at the protein level, which is dependent on PRKCQ/ PKC-u (protein kinase C, theta).…”
Section: Autophagy-deficient T Cells Fail To Enter Into S Phase Aftermentioning
confidence: 76%
“…20 It will be important to determine the effects of PDGF and proliferative status on amounts of HDAC11 protein. However, despite use of multiple cell extraction protocols (0.1% Tween-20, 1% NP-40, 6 M Urea, or 0.5% SDS containing lysis buffers) and systematic subcellular fractionation (NE-PER ™ nuclear and cytoplasmic extraction reagent, Pierce) along with use of highly concentrated cell extracts, we could not detect endogenous HDAC11 in Balb/c-3T3 or clone 2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The p27 KIP1 protein inhibits cyclin/CDK activity by binding cyclin/CDK complexes through its N-terminal, blocking ATP binding, and physically occluding the catalytic cleft of the CDK (Russo et al, 1996;Hong et al, 2009;Zhang et al, 2009). A major regulatory mechanism of controlling the p27 KIP1 inhibitory function is to regulate p27 KIP1 protein levels through transcriptional, translational, and post-translational mechanisms (Hengst and Reed, 1996;Carrano et al, 1999;Boehm et al, 2002;Bagui et al, 2009;Shin et al, 2009;Trabosh et al, 2009). Recent study revealed that a novel regulatory mechanism during postphosphorylation and polyubiquitination of proteins could be another regulatory mechanism for p27 KIP1 .…”
Section: Introductionmentioning
confidence: 99%